2007
DOI: 10.1177/0886109906295812
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Not Scary”

Abstract: To increase their research skills and confidence, students in a nonresearch-focused elective MSW course gathered qualitative data through cross-ethnic interviews for a formal research project. Qualitative findings from a focus group of students were used to examine the perspectives of the students, all but one of whom were women, about (a) changes in their knowledge of and attitudes toward research, (b) the struggles they experienced, and (c) whether such projects should be integrated into other courses. Impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…This study supports the findings of Holley (2007), Lundahl (2008) and Olsen (1990), who have emphasized important links between doing research and the development of more positive student attitudes toward learning research. Students' confusion about the nature of research and anxiety about its purported complexity are partially explained by most students' lack of practical prior experience with research.…”
Section: Implications For Teaching Researchsupporting
confidence: 92%
See 1 more Smart Citation
“…This study supports the findings of Holley (2007), Lundahl (2008) and Olsen (1990), who have emphasized important links between doing research and the development of more positive student attitudes toward learning research. Students' confusion about the nature of research and anxiety about its purported complexity are partially explained by most students' lack of practical prior experience with research.…”
Section: Implications For Teaching Researchsupporting
confidence: 92%
“…I believe that a lack of exposure was probably the biggest factor inhibiting my attitude for so long. (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) These results parallel those of Holley et al (2007), Lundahl (2008) and Olsen (1990), who reported that learning by being involved in research projects results in a more positive attitude toward the process. In particular, involvement in research, including using information derived from it, may well be a key factor in developing positive attitudes toward research.…”
Section: Factors Influencing the Development Of Positive Attitudessupporting
confidence: 89%
“…A student attempting to learn Discourse Analysis commented, "That was quite unsettling sometimes because no matter how much you read about there being no method to [Discourse Analysis], you do need, sometimes need to feel like you are doing something that is recommended or concrete and there was nothing to lean back on" (Harper, 2008, p. 203). While this student described struggling with lack of procedural guidance, others struggled with the emotional nature of some interactions with interviewees and having to manage their own emotions (Holley et al, 2007) or handle interviewees who became emotional (Roulston et al, 2003).…”
Section: Affective Dimension Of Qualitative Research Students' Learnimentioning
confidence: 96%
“…As a researcher, I have examined disadvantaged students experience of studying social work, especially in relation to pedagogy and curriculum (Newcomb et al 2017). Most research involving human services or social work students is conducted by academics and researchers and rarely is this research done or written by students themselves (Holley et al 2007). In writing about my own experience, I am not trying to speak a universal or even generalisable certainty and I do not proclaim my lived experience as the truth for all social work students or academics (Witkin 2014).…”
Section: Why An Autoethnography?mentioning
confidence: 99%